Penanganan Pengaduan Masyarakat Mengenai Pelayanan Publik - UTOMO, SAD DIAN (UI Scholars Hub, 2010)
Citizen participation is a manifestation of people empowerment, an effort to improve people’s ability in decision making, as well as an attempt to control society’s own future. Local government in Semarang is aware of such urgency of participation and thus establishes the Center of Public Service Complaint Management (CPSCM) as an institution to coordinate, implement, and manage people’s complaints of public service. This research uses qualitative approach with Amstein’s ladder of citizen participation, and Burns, Hambleton & Hogget’s ladder of citizen empowerment as the main theories. This research aims to analyze factors that influence the effectiveness of CPSCM as an instrument of citizen participation in public service; as well as to create an alternative solution to improve citizen participation. The research shows that there are five factors influencing the effectiveness of CPSCM, i. e. accommodative leadership particularly that of Semarang City’s mayor; local constitution and regulation; the role of civil society, mainly non-governmental organizations; and special events. This research also suggests some alternative solutions to improve citizen participation, such as: socializing the existence of CPSCM and establishing more transparent management of complaints; involving Local Representative Council to gain stronger legality of CPSCM; thoroughly evaluating the contribution of CPSCM for society and the government; encouraging more academic study on such complaints management institution.